Creation of “Salen-Log Counterpoint”: intercultural music between karawitan and orchestra through practice based research - Nugraha, Aditya; Sukmayadi, Yudi; Riyadi, Lanang (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
This study explores the process of creating a musical composition titled "Salen-Log Counterpoint" as an effort to adapt the aesthetics of Sundanese karawitan music within the format of a Western orchestral ensemble. The work was developed as part of an intercultural approach within the field of contemporary music composition. The aim of this study is to reveal the artistic process and technical strategies involved in transforming karawitan musical idioms into the systems and organology of the orchestra. This research employs a practice-based method, involving Wallas’ four-stage model of the creative process: preparation, incubation, illumination, and verification. The findings indicate that a contrapuntal approach combining pelog, salendro, and Western tonal systems can produce a distinct new sound texture, despite presenting technical and interpretative challenges. Adjustments in notation and playing techniques are key to maintaining a balance between aesthetic concepts and musical feasibility. This study contributes to the discourse on intercultural composition and the creative practice of integrating traditional aesthetics into contemporary musical works.